Topical oro-dispersible budesonide tablets for stricture prevention after near circumferential ESD for esophageal squamous cell cancer – a case report - Mathies, Daniel; Oyama, Tsuneo; Steinbrück, Ingo; Dumoulin, Franz Ludwig (Zeitschrift für Gastroenterologie, 2021)
Background Endoscopic resection is the treatment of choice for early esophageal cancers. However, resections comprising more than 70–80 % of the circumference are associated with a high risk of stricture formation. Currently, repetitive local injections and/or systemic steroids are given for prevention.Case report We present here the case of a 78-year-old male patient who had a near circumferential endoscopic submucosal dissection for a pT1a mm, L0, V0, R0, G2 esophageal squamous cell cancer. At the end of endoscopic resection, 80 mg of triamcinolone was injected locally. The patient was then treated with oro-dispersible budesonide tablets (2 × 1 mg/day) and nystatin (4 × 100 000 I.E.) for 8 weeks. This treatment resulted in complete healing without any stricture formation and did not result in any complications.Discussion Treatment with orodispersible budesonide tablets could help prevent strictures after large endoscopic resections in the esophagus.
Keywords: early esophageal cancer; endoscopic submucosal dissection; stricture prevention; topical steroids budesonide